Bar stress-slip relationship in reinforced concrete joints with large inelastic bar strains - Yu, Jun (2013)
Experimental results indicate that for reinforced concrete (RC) members under large deformations, such as catenary action, wide cracking and severe concrete crushing are concentrated at the beam-column connections. Bar slip at wide cracks adjacent to joint interfaces results in large fix-end rotations and discontinuity that are not included in flexural analysis. Moreover, a large slip mainly results from elongation of a bar embedded into the beam-column joints, in particular, when the bar is in post-yield stage with a large inelastic strain. For cases of continuous bars or lap-spliced bars with adequate embedment lengths in joints, bar strains at the crack interfaces can even develop up to bar fracture. Therefore, bar stress-slip relationship at the crack interfaces is very critical to accurately predict structural behavior under large deformations and rotation capacity of RC members. In this paper, a macro-bar-stress-slip model is proposed based on the assumptions that (1) the distribution of bond stress within an elastic part or an inelastic part of a reinforcing bar remains uniform; (2) the slip of a reinforcing bar at the crack interfaces is computed directly from the bar extension over the embedment length within the joints and the slip at the free end; and (3) the constitutive model of reinforcement is bilinear. In addition, the proposed model considers the effects of short embedment length and high post-yield strain on bar stress-slip relationships. The proposed model will be validated by limited pullout test results and be verified by a micro-model with consideration of local bond-slip behavior.